Crowdsourced Asparagus Urinary Odor Population Kinetics. (14th December 2017) - Ramamoorthy, Anuradha; Sadler, Brian M.; van Hasselt, J.G. Coen; Elassaiss‐Schaap, Jeroen; Kasichayanula, Sreeneeranj; Edwards, Alena Y.; van der Graaf, Piet H.; Zhang, Lei; Wagner, John A.
Abstract : The consumption of asparagus is associated with the production of malodorous urine with considerable interindividual variability (IIV). To characterize the urinary odor kinetics after consumption of asparagus spears, we conducted a study with consenting attendees from two American Society for Clinical Pharmacology and Therapeutics (ASCPT) meetings. Subjects were randomized to eat a specific number of asparagus spears, and then asked to report their urinary odor perception. Eighty‐seven subjects were included in the final analysis. A mixed effect proportional odds model was developed that adequately characterized the dose‐response relationship. We estimated the half‐life of the asparagus effect on malodorous urine to be 4.7 hours (relative standard error (RSE) = 13.2%), and identified a dose‐response slope term with good precision (24.3%). Age was found as the predictor of IIV in slope estimates. This study design and tools can be used as a demonstration "crowdsourcing" project for studying population kinetics in organizational and educational settings.